Magnesium alloy building template surface composite coating and preparation method thereof
By performing multi-layer coating treatment on magnesium alloy building formwork, forming a phosphated film and spraying modified epoxy resin and fluorocarbon resin, the problem of poor corrosion resistance and bonding performance of single coating on the surface of magnesium alloy building formwork is solved, and the problem of poor corrosion resistance and bonding performance of single coating on the surface of magnesium alloy building formwork is achieved. Higher corrosion resistance and bonding force extend the service life of the formwork and ensure the construction quality of the building walls.
Patent Information
- Application Number
- CN202411654471.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-21
AI Technical Summary
The corrosion resistance and poor bonding performance of the single coating on the surface of magnesium alloy building formwork are caused by the formwork being easily corroded and affecting the quality of building wall forming.
A multi-layer coating structure is adopted to form a phosphated film through degreasing, activation, surface conditioning and phosphating treatment, and then a composite coating is sprayed and cured separately to form a composite coating using modified epoxy resin and fluorocarbon resin composite powder as raw materials.
The corrosion resistance of magnesium alloy building formwork and the bonding force between the coating and the substrate are significantly improved, and the problem of poor anti-corrosion and bonding performance of a single coating is solved, which extends the service life of the formwork and ensures the construction quality of the building walls.
Smart Images

Figure CN119489030A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building templates for concrete engineering construction, and specifically relates to a composite coating on the surface of a magnesium alloy building template and a preparation method thereof. Background Art
[0002] Building formwork is a temporary support structure, which is made according to the design requirements to form the concrete structure and components according to the specified position and geometric size. The quality of the formwork directly affects the quality of construction projects. Magnesium alloy building formwork, also known as magnesium formwork, has been widely developed in the building formwork market in recent years after wooden formwork, steel formwork and aluminum formwork due to its light density of only 2 / 3 of aluminum and 1 / 4 of steel, high specific strength and specific stiffness, resistance to concrete alkaline corrosion, reusability, short construction period and recyclability. It is a high-quality lightweight formwork material.
[0003] Although magnesium alloy has excellent alkali resistance and the concrete is alkaline as a whole, the storage and use environment of the formwork is very complex, often in an environment containing acidic salts and easy to scratch. The chemical properties of magnesium in magnesium alloy are very active, and it is easy to undergo oxidation reaction to form loose porous films of MgO and Mg(OH)2 on its surface, which cannot provide long-term protection for magnesium alloy; at the same time, the potential of magnesium is only -2.37V, which is the lowest among all metal structural materials, so when metal magnesium comes into contact with other metals, galvanic corrosion is prone to occur. Therefore, in order to protect the surface of magnesium alloy from corrosion, preparing a protective coating on its surface is currently the most common and effective method. The application environment of magnesium alloy building formwork is complex. Concrete aggregates and on-site construction processes can easily damage the surface coating of the formwork by friction. The chemical properties of magnesium alloy itself are active. Once the surface coating of the formwork is damaged, the magnesium alloy is prone to corrosion. After pouring, pits and pockmarks will appear on the surface of the wall, which seriously affects the quality of the building wall. Therefore, magnesium alloy building formwork has very high requirements for surface treatment technology, which greatly affects the application and development of magnesium formwork in the market.
[0004] The surface treatment technologies of magnesium alloy mainly include chemical conversion film, anodizing, micro-arc oxidation, electroplating, organic coating and other technologies. Chemical conversion treatment mainly includes chromization and phosphating. Its advantages are simple operation and cheap equipment. However, due to the Cr 6+It is harmful to the human body and has serious environmental pollution. Phosphating treatment cannot be used as a protective layer for magnesium alloys and can only be used as a short-term anti-rust or coating bottom layer. Micro-arc oxidation is developed from anodizing technology. Compared with anodizing, it requires a higher voltage, the obtained film thickness is thicker and the thickness is controllable, the corrosion resistance is better, and the bonding force between the film and the substrate is also better, but anodizing and micro-arc oxidation technologies are expensive. Electroplating is also a common method for preparing surface film layers. It has the advantages of simple equipment, convenient operation, and controllable thickness and quality of the coating. However, the active electrode potential of the magnesium alloy substrate is low, and the coating is easy to form galvanic corrosion with the magnesium alloy substrate, resulting in poor bonding between the coating and the substrate. Therefore, with the development of the application of magnesium alloy building formwork, it is urgent to develop a surface treatment technology for magnesium alloy building formwork, so that the coating has strong adhesion, wear resistance, scratch resistance, corrosion resistance, and low cost, so as to improve the service life of the magnesium formwork and ensure the construction quality of the building wall.
[0005] At present, there are very few studies on the surface treatment process of magnesium alloy building templates. The main method is to apply different plastic powder coatings after using some pre-treatment processes. Because the surface of magnesium alloy is very active and easily corroded and oxidized, if the organic coating is directly applied without pre-treatment, the adhesion is not ideal, and the paint film is easy to fall off, causing difficulties in application. In addition, the anti-corrosion performance and surface properties of different plastic powders are different. For example, although a single epoxy resin coating has good corrosion resistance, adhesion and impact resistance, its weather resistance is poor. At present, in the field where weather resistance and corrosion resistance are required to be relatively high, a double-layer spraying method is generally used on the market, that is, a bottom layer anti-corrosion coating and a surface layer weather-resistant coating. For example, the Chinese patent with the authorization number CN111500148B discloses a functional heavy anti-corrosion water-based coating for steel modified by graphene and its preparation method and use method. After the steel surface is rusted and degreased, an epoxy resin and fluorocarbon resin composite coating is sprayed. However, the production process and process control of the present invention are relatively complex, the spraying conditions are required to be relatively high, and the interlayer adhesion is likely to be poor, and the process control is relatively difficult. Summary of the invention
[0006] The purpose of the present invention is to provide a composite coating on the surface of a magnesium alloy building template and a preparation method thereof, so as to solve the technical problems of poor corrosion resistance and poor bonding performance with the substrate of a single coating on the surface of the magnesium alloy building template.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing a composite coating on the surface of a magnesium alloy building template, comprising the following steps: The magnesium template is subjected to degreasing treatment, activation treatment, surface conditioning treatment and phosphating treatment in sequence to form a phosphating film on the surface of the magnesium template; Using modified epoxy resin composite powder as raw material, a modified epoxy resin coating is prepared on the surface of the phosphating film; The fluorocarbon resin composite powder was used as raw material to prepare a fluorocarbon resin coating on the surface of a modified epoxy resin coating to obtain a composite coating on the surface of a magnesium alloy building formwork.
[0008] Furthermore, the degreasing treatment is to place the magnesium template into a degreasing solution for degreasing treatment; The mass concentration of the degreasing solution is 5% to 10%, and the pH value is 11 to 13; the degreasing treatment is carried out at room temperature for 10 to 20 minutes; The activation treatment is to wash the magnesium template after degreasing treatment and then put it into the activation solution for activation treatment; The mass concentration of the activation solution is 5% to 10%, and the pH value is 1 to 2; the activation treatment is performed at room temperature for 60 to 120 seconds.
[0009] Furthermore, the degreasing solution comprises: 3-10 g / L sodium hydroxide, 3-10 g / L sodium carbonate, 3-10 g / L sodium silicate, 3-10 g / L sodium pyrophosphate, 0.1-1 g / L sodium dodecyl sulfate, and the rest is water; The activation solution comprises: 80-160 g / L of ammonium bifluoride, 50-100 g / L of hydrofluoric acid, 20-50 g / L of phosphoric acid, and the remainder is water.
[0010] Furthermore, the surface conditioning treatment is to wash the magnesium template after the activation treatment and then put it into a surface conditioning solution for surface conditioning treatment; The mass concentration of the surface conditioning solution is 5% to 10%, and the pH value is 9 to 10; the temperature of the surface conditioning treatment is 50 to 80°C, and the time is 2 to 5 minutes; The surface conditioning solution comprises: 5-20 g / L sodium tripolyphosphate, 10-50 g / L sodium hydroxide, 2-10 g / L sodium nitrate, 3-16 g / L potassium pyrophosphate, and the rest is water.
[0011] Furthermore, the phosphating treatment is to wash the magnesium template after the surface conditioning treatment and then put it into a phosphating solution for phosphating treatment; The mass concentration of the phosphating solution is 5% to 10%, and the pH value is 5 to 6; the phosphating treatment is carried out at room temperature for 60 to 120 seconds; After the phosphating treatment is performed for cleaning, a heating treatment is further included; the heating treatment is baking at 200-220° C. for 20-30 minutes; The phosphating solution comprises: 0.01-0.5 mol phosphoric acid, 5-50 g / L ammonium dihydrogen phosphate, 0.5-10 g / L sodium silicate, 0.5-10 g / L sodium molybdate, 3-5 g / L citric acid, 0.1-1 g / L ammonium metavanadate, and the rest is water.
[0012] Furthermore, the specific steps of preparing the modified epoxy resin coating on the surface of the phosphating film using the modified epoxy resin composite powder as raw material are as follows: The modified epoxy resin composite powder is sprayed on the surface of the phosphating film by using an electrostatic spraying method, and then solidified, heat-insulated and cooled in sequence to obtain a modified epoxy resin coating; The spraying thickness of the modified epoxy resin composite powder on the surface of the phosphate film is 30-40 μm; the curing temperature is 150-180° C.; the heat preservation time is 10-30 min; the cooling treatment method is to cool to room temperature with the furnace; The components of the modified epoxy resin composite powder include, by mass: 100 parts of modified bisphenol A epoxy resin, 20 parts of modified dicyandiamide curing agent, 15 parts of silica microstone powder, 7.5 parts of mica powder, 2.5 parts of titanium dioxide, 0.2 parts of degassing agent, 0.5 parts of leveling agent, 0.1-0.2 parts of plasticizer, 0.1-0.2 parts of curing accelerator, and 0.3 parts of defoaming agent.
[0013] Furthermore, in the modified epoxy resin composite powder, the degassing agent is diphenyl ether; the leveling agent is polyacrylate; the plasticizer is polyvinyl butyral; the curing accelerator is 2-methylimidazole; and the defoaming agent is HW601.
[0014] Furthermore, the specific steps of using fluorocarbon resin composite powder as raw material to prepare fluorocarbon resin coating on the surface of modified epoxy resin coating to obtain composite coating on the surface of magnesium alloy building formwork are: The fluorocarbon resin composite powder is sprayed on the surface of the modified epoxy resin coating by using an electrostatic spraying method, and then solidified, heat-insulated and cooled in sequence to obtain the fluorocarbon resin coating; The spraying thickness of the fluorocarbon resin composite powder on the surface of the modified epoxy resin coating is 60-80 μm; the curing temperature is 180-210° C.; the heat preservation time is 20-30 minutes; and the cooling treatment method is to cool to room temperature with the furnace; The components of the fluorocarbon resin composite powder include, by mass: Fluorocarbon resin 60%, isocyanate curing agent 13.3%, superfine barium sulfate 3.2%, rutile titanium dioxide 20%, ultramarine 1%, degassing agent 0.8%, leveling agent 1.5%, catalyst 0.2%, defoaming agent 0.3%, light stabilizer 0.3%, antioxidant 0.3%, UV absorber 0.3%.
[0015] Furthermore, in the fluorocarbon resin composite powder, the degassing agent is dibenzoyl ketone; the leveling agent is polyacrylate; the catalyst is an organic zirconium catalyst; the defoaming agent is an organic silicon defoaming agent; the light stabilizer is rutile titanium dioxide, carbon blue or SiO2; the antioxidant is AS130; and the ultraviolet absorber is o-hydroxybenzophenone.
[0016] The invention also discloses a composite coating on the surface of a magnesium alloy building template prepared by the preparation method.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a composite coating on the surface of a magnesium alloy building template. First, the magnesium template is subjected to degreasing treatment, activation treatment, surface conditioning treatment and phosphating treatment in sequence to form a phosphating film on the surface of the magnesium template, and a dense protective film is prepared on the surface of the magnesium template to improve the corrosion resistance of the magnesium template and the bonding force with the modified epoxy resin coating; then, modified epoxy resin composite powder and fluorocarbon resin composite powder are used as raw materials in sequence to prepare a modified epoxy resin coating and a fluorocarbon resin coating, and a composite coating is obtained on the surface of the magnesium alloy building template. Since the epoxy value of the epoxy resin is relatively high, the cross-linking density of the cured product is high, and after the epoxy resin in the invention is added with a modifier, the content of macromolecular segments in the epoxy resin is reduced, the relative molecular mass distribution is narrower, and the modified epoxy resin and fluorocarbon resin composite powder are used as raw materials in sequence to prepare a modified epoxy resin coating and a fluorocarbon resin coating, and a composite coating is obtained on the surface of the magnesium alloy building template. The molecular structure of the epoxy resin contains more polar groups such as hydroxyl groups, which increases the adhesion of the modified epoxy resin. At the same time, since the baking temperature of the modified epoxy resin composite powder is 150-180°C, the resin is not completely cured at this time. After spraying the fluorocarbon resin composite powder, it is cured as a whole at 210°C. At this time, the two resins will melt and combine, and there will be molecular migration and diffusion, and mutual penetration to achieve overall bonding. The internal stress generated during the curing and cooling process is small, so that the bonding between the coatings is better. Therefore, it can effectively improve the corrosion resistance of the magnesium formwork and the bonding with the fluorocarbon resin coating, and solve the technical problems of poor anti-corrosion performance of a single coating on the magnesium alloy building formwork and poor bonding performance with the substrate, and poor bonding between composite coatings.
[0018] Furthermore, the modified epoxy resin composite powder and fluorocarbon resin composite powder used in the present invention retain the main characteristics of each component and improve the various properties of the coating by adding various additives, and are comprehensive functional anti-corrosion materials; the preparation method of the present invention has simple equipment, easy operation, low cost, and is suitable for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The present invention is a flow chart for preparing the composite coating on the surface of the magnesium alloy building template; Figure 2 This is a spraying effect diagram of the composite coating on the surface of the magnesium alloy building formwork in Example 1 of the present invention. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0021] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0022] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values within the range (including integers and fractions).
[0023] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0024] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0025] like Figure 1 As shown, the present invention provides a method for preparing a composite coating on the surface of a magnesium alloy building template, comprising the following steps: S1: Degreasing treatment: put the magnesium template into a degreasing solution with a mass concentration of 5-10% and a pH value of 11-13, and treat it at room temperature for 10-20 minutes to remove surface grease and dust; S2: Activation treatment: After the degreased magnesium template is washed twice in a clean water tank, it is placed in an activation solution with a mass concentration of 5-10% and a pH value of 1-2. The activation solution is treated at room temperature for 60-120 seconds to remove impurities and oxides on the surface of the magnesium template, making the surface cleaner and more active and neutralizing the residual alkali in the previous step; S3: Surface conditioning treatment: After the activated magnesium template is washed twice in a clean water tank, it is placed in a surface conditioning solution with a mass concentration of 5-10% for surface conditioning bleaching treatment. The pH value of the surface conditioning solution is 9-10, the temperature is controlled at 50-80°C, and the treatment time is 2-5 minutes. The acidic substances remaining in the holes of the magnesium template after micro-etching are neutralized and trace impurities on the surface are removed, so that the color of the magnesium alloy surface is uniform, so as to improve the adhesion of the subsequent phosphating film; S4: Phosphating treatment: After the magnesium template after surface conditioning is washed twice in a clean water tank, it is placed in a phosphating solution with a mass concentration of 5-10%, and the pH value of the phosphating solution is 5-6. The treatment is carried out at room temperature for 60-120 seconds, and then washed twice in a clean water tank, and then placed in a heating furnace for baking at 200-220°C for 20-30 minutes. After cooling to room temperature in the furnace, it is taken out. A dense phosphating film is formed on the surface of the magnesium template, which better improves the corrosion resistance of the magnesium template and the bonding strength with the modified epoxy resin coating; S5: modified epoxy resin composite powder spraying: the modified epoxy resin composite powder is sprayed on the surface of the phosphate film by electrostatic spraying method using a spray gun, the coating thickness is about 30~40μm, and then the magnesium template is placed at 150~180℃ for curing, kept warm for 10~30min, and cooled to room temperature with the furnace to form a layer of modified epoxy resin coating on the surface of the magnesium template; S6: Fluorocarbon resin composite powder spraying: The prepared fluorocarbon resin composite powder is sprayed on the surface of the modified epoxy resin coating with a spray gun by electrostatic spraying method. The coating thickness is about 60~80μm. Then the magnesium template is placed at 180~210℃ for curing, kept warm for 20~30 min, and cooled to room temperature with the furnace to form a layer of fluorocarbon resin coating on the surface of the modified epoxy resin coating.
[0026] Preferably, in S1, the degreasing solution is composed of components with the following concentrations: 3-10 g / L sodium hydroxide, 3-10 g / L sodium carbonate, 3-10 g / L sodium silicate, 3-10 g / L sodium pyrophosphate, 0.1-1 g / L sodium dodecyl sulfate, and the rest is water; wherein sodium dodecyl sulfate is used as a surfactant to promote uniform dispersion of the active ingredients, more consistent pores, and cleaner cleaning.
[0027] Preferably, in S2, the activation solution is composed of components with the following concentrations: 80-160 g / L of ammonium bifluoride, 50-100 g / L of hydrofluoric acid, 20-50 g / L of phosphoric acid, and the rest is water.
[0028] Preferably, in S3, the surface conditioning solution is composed of components with the following concentrations: 5-20 g / L sodium tripolyphosphate, 10-50 g / L sodium hydroxide, 2-10 g / L sodium nitrate, 3-16 g / L potassium pyrophosphate, and the rest is water; wherein sodium nitrate as a corrosion inhibitor can effectively adjust the reaction rate and make the pores form uniform and dense.
[0029] Preferably, in S4, the phosphating solution is composed of components with the following concentrations: 0.01-0.5 mol phosphoric acid, 5-50 g / L diammonium phosphate, 0.5-10 g / L sodium silicate, 0.5-10 g / L sodium molybdate, 3-5 g / L citric acid, 0.1-1 g / L ammonium metavanadate, and the rest is water.
[0030] Preferably, the addition of citric acid can better improve the bonding strength and corrosion resistance of the phosphate film on the surface of the magnesium alloy.
[0031] Preferably, in S5, the modified epoxy resin coating is composed of modified bisphenol A epoxy resin, modified dicyandiamide curing agent, silica microstone powder, mica powder, titanium dioxide, degassing agent, leveling agent, plasticizer, curing accelerator, defoaming agent and other additives. The prepared modified epoxy resin coating has excellent adhesion, corrosion resistance and good impact resistance.
[0032] Preferably, 100 parts of modified bisphenol A epoxy resin, 20 parts of modified dicyandiamide curing agent, 15 parts of silica microstone powder, 7.5 parts of mica powder, 2.5 parts of titanium dioxide, 0.2 parts of degassing agent, 0.5 parts of leveling agent, 0.1-0.2 parts of plasticizer, 0.1-0.2 parts of curing accelerator, and 0.3 parts of defoaming agent.
[0033] Preferably, the epoxy resin is a modified bisphenol A epoxy resin. The modified epoxy resin has a lower melting viscosity when heated and is easier to flow. In addition, more polar groups such as hydroxyl groups in the resin molecules increase the adhesion.
[0034] Preferably, the titanium dioxide is pre-treated with a surfactant silane coupling agent and fully dried before being mixed with other materials to improve compatibility with the epoxy resin.
[0035] Preferably, the degassing agent is benzoin, commonly known as "benzoin".
[0036] Preferably, the leveling agent is polyacrylate.
[0037] Preferably, the plasticizer is polyvinyl butyral.
[0038] Preferably, the curing accelerator is 2-methylimidazole.
[0039] Preferably, the defoaming agent is HW601.
[0040] Preferably, in S6, the fluorocarbon resin coating is fluorocarbon resin, isocyanate curing agent, ultrafine barium sulfate, rutile titanium dioxide, ultramarine, degassing agent, leveling agent, catalyst, defoaming agent, light stabilizer, antioxidant, and ultraviolet absorber.
[0041] Preferably, the fluorocarbon resin comprises 60%, isocyanate curing agent 13.3%, superfine barium sulfate 3.2%, rutile titanium dioxide 20%, ultramarine 1%, deaerator 0.8%, leveling agent 1.5%, catalyst 0.2%, defoamer 0.3%, light stabilizer 0.3%, antioxidant 0.3%, and ultraviolet absorber 0.3%.
[0042] Preferably, the degassing agent is benzoin, commonly known as "benzoin".
[0043] Preferably, the leveling agent is polyacrylate.
[0044] Preferably, the catalyst is an organozirconium catalyst.
[0045] Preferably, the defoamer is a silicone defoamer Preferably, the light stabilizer is rutile titanium dioxide, carbon blue or SiO2.
[0046] Preferably, the antioxidant is AS130.
[0047] Preferably, the ultraviolet absorber is o-hydroxybenzophenone.
[0048] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0049] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0050] Example 1 A method for preparing a composite coating on the surface of a magnesium alloy building template comprises the following steps: The magnesium alloy material used for the magnesium alloy building formwork is AZ41M: Prepare degreasing solution: 8g / L sodium hydroxide, 8g / L sodium carbonate, 8g / L sodium silicate, 8g / L sodium pyrophosphate, 0.5g / L sodium dodecyl sulfate, and the rest water, and prepare them in the treatment tank according to the proportion, with a mass concentration of 8%, a pH of 12, and room temperature; Prepare activation solution: 120g / L ammonium bifluoride, 80g / L hydrofluoric acid, 40g / L phosphoric acid, and the rest water are mixed in the treatment tank according to the ratio, with a mass concentration of 8%, a pH of 2, and room temperature; Prepare the surface adjustment solution: 8g / L sodium tripolyphosphate, 15g / L sodium hydroxide, 5g / L sodium nitrate, 6g / L potassium pyrophosphate, and the rest water, mix them in the treatment tank according to the ratio, the mass concentration is 8%, the pH is 10, and heat to 75℃; Prepare phosphating solution: 0.2mol phosphoric acid, 10g / L ammonium dihydrogen phosphate, 5g / L sodium silicate, 3g / L sodium molybdate, 3g / L citric acid, 0.3g / L ammonium metavanadate, and the rest water are prepared in the treatment tank according to the proportion, with a mass concentration of 8%, a pH of 5, and room temperature; The magnesium template was placed in a degreasing agent solution with a mass concentration of 8% and treated at room temperature for 15 minutes; after being washed twice in a clean water tank, it was placed in an activation solution with a mass concentration of 8% and treated at room temperature for 100 seconds to remove impurities and oxides on the surface of the magnesium template, making the surface cleaner and more active and neutralizing the residual alkali in the previous step; after being washed twice in a clean water tank, it was placed in a surface conditioning solution with a mass concentration of 8% and treated at 75°C for 150 seconds; after being washed twice in a clean water tank, it was placed in a phosphating solution with a mass concentration of 8% for phosphating treatment, treated at room temperature for 100 seconds, and then baked at 220°C for 25 minutes to form a dense phosphating film, which better improves the corrosion resistance of the magnesium template and the bonding strength with the modified epoxy resin coating; Prepare modified epoxy resin composite powder: 100 parts of modified bisphenol A epoxy resin, 20 parts of modified dicyandiamide, 15 parts of silica microstone powder, 7.5 parts of mica powder, 2.5 parts of titanium dioxide, 0.2 parts of degassing agent, 0.5 parts of leveling agent, 0.1 parts of plasticizer, 0.1 parts of curing accelerator, 0.3 parts of defoaming agent and other auxiliary agents; The magnesium template with a dense phosphate film formed on the surface after baking is electrostatically sprayed with a spray gun to spray the prepared modified epoxy resin composite powder on the surface of the magnesium template, with a spray thickness of 35μm; then the metal workpiece is cured at 180℃, kept warm for 20min, and cooled to room temperature with the furnace to form a modified epoxy resin coating on the surface of the magnesium template; Fluorocarbon resin composite powder: 60% fluorocarbon resin, 13.3% isocyanate curing agent, 3.2% superfine barium sulfate, 20% rutile titanium dioxide, 1% ultramarine, 0.8% degassing agent, 1.5% leveling agent, 0.2% catalyst, 0.3% defoaming agent, 0.3% light stabilizer, 0.3% antioxidant, 0.3% ultraviolet absorber. The magnesium template whose surface has been cured to form a layer of modified epoxy resin coating is electrostatically sprayed with a spray gun to spray the prepared fluorocarbon resin composite powder on the surface of the magnesium template, with a spraying thickness of 75μm; the metal workpiece is then cured at 200℃, kept warm for 30 minutes, and cooled to room temperature with the furnace to form a layer of fluorocarbon resin coating on the surface of the magnesium template.
[0051] The spraying effect obtained by the surface treatment process of the present invention is as follows: Figure 2 It can be seen that after the surface treatment process of the present invention, a 5% NaCl salt spray test is carried out, and the salt spray resistance can reach 720h, and the coating has no cracking, shedding, or blistering.
[0052] Example 2 A method for preparing a composite coating on the surface of a magnesium alloy building template comprises the following steps: The magnesium alloy material used for the magnesium alloy building formwork is AZ41M: Prepare degreasing solution: 10g / L sodium hydroxide, 10g / L sodium carbonate, 10g / L sodium silicate, 10g / L sodium pyrophosphate, 1g / L sodium dodecyl sulfate, and the rest water are mixed in the treatment tank according to the proportion, with a mass concentration of 10%, a pH of 13, and room temperature; Prepare activation solution: 160g / L ammonium bifluoride, 100g / L hydrofluoric acid, 50g / L phosphoric acid, and the rest water are mixed in the treatment tank according to the ratio, with a mass concentration of 10%, a pH of 1, and room temperature; Prepare the surface adjustment solution: 20g / L sodium tripolyphosphate, 50g / L sodium hydroxide, 10g / L sodium nitrate, 16g / L potassium pyrophosphate, and the rest water, mix them in the treatment tank according to the proportion, the mass concentration is 10%, the pH is 10, and heat to 50℃; Prepare phosphating solution: 0.5mol phosphoric acid, 50g / L ammonium dihydrogen phosphate, 10g / L sodium silicate, 10g / L sodium molybdate, 5g / L citric acid, 1g / L ammonium metavanadate, and the rest is water, and prepare in the treatment tank according to the proportion, the mass concentration is 10%, the pH is 5, and the temperature is room temperature; The magnesium template is placed in a degreasing agent solution with a mass concentration of 10%, and the treatment time at room temperature is 10 minutes; after being washed twice in a clean water tank, it is placed in an activation solution with a mass concentration of 10%, and treated at room temperature for 60 seconds to remove impurities and oxides on the surface of the magnesium template, making the surface cleaner and more active and neutralizing the residual alkali in the previous step; after being washed twice in a clean water tank, it is placed in a surface conditioning solution with a mass concentration of 10%, and treated at 50°C for 5 minutes; after being washed twice in a clean water tank, it is placed in a phosphating solution with a mass concentration of 10% for phosphating treatment, treated at room temperature for 60 seconds, and then baked at 200°C for 30 minutes to form a dense phosphating film, which better improves the corrosion resistance of the magnesium template and the bonding strength with the modified epoxy resin coating; Prepare modified epoxy resin composite powder: 100 parts of modified bisphenol A epoxy resin, 20 parts of modified dicyandiamide, 15 parts of silica microstone powder, 7.5 parts of mica powder, 2.5 parts of titanium dioxide, 0.2 parts of degassing agent, 0.5 parts of leveling agent, 0.1 parts of plasticizer, 0.1 parts of curing accelerator, 0.3 parts of defoaming agent and other auxiliary agents; The magnesium template with a dense phosphate film formed on the surface after baking is electrostatically sprayed with a spray gun to spray the prepared modified epoxy resin composite powder on the surface of the magnesium template, with a spray thickness of 30μm; then the metal workpiece is cured at 150℃, kept warm for 30min, and cooled to room temperature with the furnace to form a modified epoxy resin coating on the surface of the magnesium template; Fluorocarbon resin composite powder: 60% fluorocarbon resin, 13.3% isocyanate curing agent, 3.2% superfine barium sulfate, 20% rutile titanium dioxide, 1% ultramarine, 0.8% degassing agent, 1.5% leveling agent, 0.2% catalyst, 0.3% defoaming agent, 0.3% light stabilizer, 0.3% antioxidant, 0.3% ultraviolet absorber. The magnesium template whose surface has been cured to form a layer of modified epoxy resin coating is electrostatically sprayed with a spray gun to spray the prepared fluorocarbon resin composite powder on the surface of the magnesium template, with a spraying thickness of 70μm; then the metal workpiece is cured at 200℃, kept warm for 30min, and cooled to room temperature with the furnace to form a layer of fluorocarbon resin coating on the surface of the magnesium template.
[0053] Example 3 A method for preparing a composite coating on the surface of a magnesium alloy building template comprises the following steps: The magnesium alloy material used for the magnesium alloy building formwork is AZ41M: Prepare degreasing solution: 3g / L sodium hydroxide, 3g / L sodium carbonate, 3g / L sodium silicate, 3g / L sodium pyrophosphate, 0.1g / L sodium dodecyl sulfate, and the rest water, and prepare them in the treatment tank according to the proportion, with a mass concentration of 5%, a pH of 11, and room temperature; Prepare activation solution: 80g / L ammonium bifluoride, 50g / L hydrofluoric acid, 20g / L phosphoric acid, and the rest water are mixed in the treatment tank according to the ratio, with a mass concentration of 5%, a pH of 2, and room temperature; Prepare the surface adjustment solution: 5g / L sodium tripolyphosphate, 10g / L sodium hydroxide, 2g / L sodium nitrate, 3g / L potassium pyrophosphate, and the rest water, mix them in the treatment tank according to the proportion, the mass concentration is 5%, the pH is 9, and heat to 80℃; Prepare phosphating solution: 0.2mol phosphoric acid, 30g / L ammonium dihydrogen phosphate, 8g / L sodium silicate, 8g / L sodium molybdate, 4g / L citric acid, 0.8g / L ammonium metavanadate, and the rest is water, and prepare in the treatment tank according to the proportion, with a mass concentration of 5%, a pH of 6, and room temperature; The magnesium template is placed in a degreasing agent solution with a mass concentration of 5% and treated at room temperature for 20 minutes; after being washed twice in a clean water tank, it is placed in an activation solution with a mass concentration of 5% and treated at room temperature for 120 seconds to remove impurities and oxides on the surface of the magnesium template, making the surface cleaner and more active and neutralizing the residual alkali in the previous step; after being washed twice in a clean water tank, it is placed in a surface conditioning solution with a mass concentration of 5% and treated at 80°C for 120 seconds; after being washed twice in a clean water tank, it is placed in a phosphating solution with a mass concentration of 5% for phosphating treatment, treated at room temperature for 120 seconds, and then baked at 220°C for 20 minutes to form a dense phosphating film, which better improves the corrosion resistance of the magnesium template and the bonding strength with the modified epoxy resin coating; Prepare modified epoxy resin composite powder: 100 parts of modified bisphenol A epoxy resin, 20 parts of modified dicyandiamide, 15 parts of silica microstone powder, 7.5 parts of mica powder, 2.5 parts of titanium dioxide, 0.2 parts of degassing agent, 0.5 parts of leveling agent, 0.1 parts of plasticizer, 0.1 parts of curing accelerator, 0.3 parts of defoaming agent and other auxiliary agents; The magnesium template with a dense phosphate film formed on the surface after baking is electrostatically sprayed with a spray gun to spray the prepared modified epoxy resin composite powder on the surface of the magnesium template, with a spray thickness of 40μm; then the metal workpiece is cured at 180℃, kept warm for 25min, and cooled to room temperature with the furnace to form a modified epoxy resin coating on the surface of the magnesium template; Fluorocarbon resin composite powder: 60% fluorocarbon resin, 13.3% isocyanate curing agent, 3.2% superfine barium sulfate, 20% rutile titanium dioxide, 1% ultramarine, 0.8% degassing agent, 1.5% leveling agent, 0.2% catalyst, 0.3% defoaming agent, 0.3% light stabilizer, 0.3% antioxidant, 0.3% ultraviolet absorber. The magnesium template whose surface has been cured to form a layer of modified epoxy resin coating is electrostatically sprayed with a spray gun to spray the prepared fluorocarbon resin composite powder on the surface of the magnesium template, with a spraying thickness of 60μm; then the metal workpiece is cured at 200℃, kept warm for 30 minutes, and cooled to room temperature with the furnace to form a layer of fluorocarbon resin coating on the surface of the magnesium template.
[0054] Example 4 A method for preparing a composite coating on the surface of a magnesium alloy building template comprises the following steps: The magnesium alloy material used for the magnesium alloy building formwork is AZ41M: Prepare degreasing solution: 6g / L sodium hydroxide, 6g / L sodium carbonate, 6g / L sodium silicate, 6g / L sodium pyrophosphate, 0.3g / L sodium dodecyl sulfate, and the rest water, and prepare them in the treatment tank according to the proportion, with a mass concentration of 10%, a pH of 12, and room temperature; Prepare activation solution: 100g / L ammonium bifluoride, 60g / L hydrofluoric acid, 30g / L phosphoric acid, and the rest water are mixed in the treatment tank according to the ratio, with a mass concentration of 10%, a pH of 1.5, and room temperature; Prepare the surface adjustment solution: 15g / L sodium tripolyphosphate, 30g / L sodium hydroxide, 8g / L sodium nitrate, 10g / L potassium pyrophosphate, and the rest water, mix them in the treatment tank according to the proportion, the mass concentration is 10%, the pH is 10, and heat to 60℃; Prepare phosphating solution: 0.01mol phosphoric acid, 50g / L ammonium dihydrogen phosphate, 10g / L sodium silicate, 10g / L sodium molybdate, 5g / L citric acid, 0.8g / L ammonium metavanadate, and the rest is water, and prepare in the treatment tank according to the proportion, the mass concentration is 10%, the pH is 5, and the temperature is room temperature; The magnesium template is placed in a degreasing agent solution with a mass concentration of 10%, and the treatment time at room temperature is 10 minutes; after being washed twice in a clean water tank, it is placed in an activation solution with a mass concentration of 10%, and treated at room temperature for 70 seconds to remove impurities and oxides on the surface of the magnesium template, making the surface cleaner and more active and neutralizing the residual alkali in the previous step; after being washed twice in a clean water tank, it is placed in a surface conditioning solution with a mass concentration of 10%, and treated at 60°C for 4 minutes; after being washed twice in a clean water tank, it is placed in a phosphating solution with a mass concentration of 10% for phosphating treatment, and after being treated at room temperature for 60 seconds, it is baked at 200°C for 30 minutes to form a dense phosphating film, which better improves the corrosion resistance of the magnesium template and the bonding strength with the modified epoxy resin coating; Prepare modified epoxy resin composite powder: 100 parts of modified bisphenol A epoxy resin, 20 parts of modified dicyandiamide, 15 parts of silica microstone powder, 7.5 parts of mica powder, 2.5 parts of titanium dioxide, 0.2 parts of degassing agent, 0.5 parts of leveling agent, 0.1 parts of plasticizer, 0.1 parts of curing accelerator, 0.3 parts of defoaming agent and other auxiliary agents; The magnesium template with a dense phosphate film formed on the surface after baking is electrostatically sprayed with a spray gun to spray the prepared modified epoxy resin composite powder on the surface of the magnesium template, with a spray thickness of 30μm; then the metal workpiece is cured at 150℃, kept warm for 30min, and cooled to room temperature with the furnace to form a modified epoxy resin coating on the surface of the magnesium template; Fluorocarbon resin composite powder: 60% fluorocarbon resin, 13.3% isocyanate curing agent, 3.2% superfine barium sulfate, 20% rutile titanium dioxide, 1% ultramarine, 0.8% degassing agent, 1.5% leveling agent, 0.2% catalyst, 0.3% defoaming agent, 0.3% light stabilizer, 0.3% antioxidant, 0.3% ultraviolet absorber. The magnesium template whose surface has been cured to form a modified epoxy resin coating is electrostatically sprayed with a spray gun to spray the prepared fluorocarbon resin composite powder on the surface of the magnesium template, with a spraying thickness of 80μm; then the metal workpiece is cured at 210℃, kept warm for 30 minutes, and cooled to room temperature with the furnace to form a fluorocarbon resin coating on the surface of the magnesium template.
[0055] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a composite coating on the surface of a magnesium alloy building template, characterized in that: The following steps are involved: The magnesium template is subjected to degreasing treatment, activation treatment, surface conditioning treatment and phosphating treatment in sequence to form a phosphating film on the surface of the magnesium template; Using modified epoxy resin composite powder as raw material, a modified epoxy resin coating is prepared on the surface of the phosphating film; The fluorocarbon resin composite powder was used as raw material to prepare a fluorocarbon resin coating on the surface of a modified epoxy resin coating to obtain a composite coating on the surface of a magnesium alloy building formwork.
2. The method for preparing a composite coating on the surface of a magnesium alloy building template according to claim 1, characterized in that: The degreasing treatment is to place the magnesium template into a degreasing solution for degreasing treatment; The mass concentration of the degreasing solution is 5% to 10%, and the pH value is 11 to 13; the degreasing treatment is carried out at room temperature for 10 to 20 minutes; The activation treatment is to wash the magnesium template after degreasing treatment and then put it into the activation solution for activation treatment; The mass concentration of the activation solution is 5% to 10%, and the pH value is 1 to 2; the activation treatment is performed at room temperature for 60 to 120 seconds.
3. The method for preparing a composite coating on the surface of a magnesium alloy building template according to claim 2, characterized in that: The degreasing solution comprises: 3-10 g / L sodium hydroxide, 3-10 g / L sodium carbonate, 3-10 g / L sodium silicate, 3-10 g / L sodium pyrophosphate, 0.1-1 g / L sodium dodecyl sulfate, and the rest is water; The activation solution comprises: 80-160 g / L of ammonium bifluoride, 50-100 g / L of hydrofluoric acid, 20-50 g / L of phosphoric acid, and the remainder is water.
4. The method for preparing a composite coating on the surface of a magnesium alloy building formwork according to claim 1, characterized in that: The surface conditioning treatment is to wash the magnesium template after the activation treatment and then put it into the surface conditioning solution for surface conditioning treatment; The mass concentration of the surface conditioning solution is 5% to 10%, and the pH value is 9 to 10; the temperature of the surface conditioning treatment is 50 to 80°C, and the time is 2 to 5 minutes; The surface conditioning solution comprises: 5-20 g / L sodium tripolyphosphate, 10-50 g / L sodium hydroxide, 2-10 g / L sodium nitrate, 3-16 g / L potassium pyrophosphate, and the rest is water.
5. The method for preparing a composite coating on the surface of a magnesium alloy building formwork according to claim 1, characterized in that: The phosphating treatment is to clean the magnesium template after the surface conditioning treatment and then put it into the phosphating solution for phosphating treatment; The mass concentration of the phosphating solution is 5% to 10%, and the pH value is 5 to 6; the phosphating treatment is carried out at room temperature for 60 to 120 seconds; After the phosphating treatment is performed for cleaning, a heating treatment is further included; the heating treatment is baking at 200-220° C. for 20-30 minutes; The phosphating solution comprises: 0.01-0.5 mol phosphoric acid, 5-50 g / L ammonium dihydrogen phosphate, 0.5-10 g / L sodium silicate, 0.5-10 g / L sodium molybdate, 3-5 g / L citric acid, 0.1-1 g / L ammonium metavanadate, and the rest is water.
6. The method for preparing a composite coating on the surface of a magnesium alloy building formwork according to claim 1, characterized in that: The specific steps of preparing the modified epoxy resin coating on the surface of the phosphating film using the modified epoxy resin composite powder as raw material are as follows: The modified epoxy resin composite powder is sprayed on the surface of the phosphating film by using an electrostatic spraying method, and then solidified, heat-insulated and cooled in sequence to obtain a modified epoxy resin coating; The spraying thickness of the modified epoxy resin coating on the surface of the phosphate film is 30-40 μm; the curing temperature is 150-180° C.; the heat preservation time is 10-30 min; the cooling treatment method is to cool to room temperature with the furnace; The components of the modified epoxy resin composite powder include, by mass: 100 parts of modified bisphenol A epoxy resin, 20 parts of modified dicyandiamide curing agent, 15 parts of silica microstone powder, 7.5 parts of mica powder, 2.5 parts of titanium dioxide, 0.2 parts of degassing agent, 0.5 parts of leveling agent, 0.1-0.2 parts of plasticizer, 0.1-0.2 parts of curing accelerator, and 0.3 parts of defoaming agent.
7. The method for preparing a composite coating on the surface of a magnesium alloy building formwork according to claim 6, characterized in that: In the modified epoxy resin composite powder, the degassing agent is benzoic acid ketone; the leveling agent is polyacrylate; the plasticizer is polyvinyl butyral; the curing accelerator is 2-methylimidazole; and the defoaming agent is HW601.
8. The method for preparing a composite coating on the surface of a magnesium alloy building formwork according to claim 1, characterized in that: The specific steps of using fluorocarbon resin composite powder as raw material to prepare fluorocarbon resin coating on the surface of modified epoxy resin coating to obtain composite coating on the surface of magnesium alloy building template are as follows: The fluorocarbon resin composite powder is sprayed on the surface of the modified epoxy resin coating by using an electrostatic spraying method, and then solidified, heat-insulated and cooled in sequence to obtain the fluorocarbon resin coating; The spraying thickness of the fluorocarbon resin composite powder on the surface of the modified epoxy resin coating is 60-80 μm; the curing temperature is 180-210° C.; the heat preservation time is 20-30 minutes; and the cooling treatment method is to cool to room temperature with the furnace; The components of the fluorocarbon resin composite powder include, by mass: Fluorocarbon resin 60%, isocyanate curing agent 13.3%, superfine barium sulfate 3.2%, rutile titanium dioxide 20%, ultramarine 1%, degassing agent 0.8%, leveling agent 1.5%, catalyst 0.2%, defoaming agent 0.3%, light stabilizer 0.3%, antioxidant 0.3%, UV absorber 0.3%.
9. The method for preparing a composite coating on the surface of a magnesium alloy building template according to claim 8, characterized in that: In the fluorocarbon resin composite powder, the degassing agent is dibenzoyl ketone; the leveling agent is polyacrylate; the catalyst is an organic zirconium catalyst; the defoaming agent is an organic silicon defoaming agent; the light stabilizer is rutile titanium dioxide, carbon blue or SiO2; the antioxidant is AS130; and the ultraviolet absorber is o-hydroxybenzophenone.
10. A composite coating on the surface of a magnesium alloy building formwork, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
A graphene-modified functional heavy-duty anti-corrosion waterborne coating for steel, its preparation method and application method.
CN111500148B